Felfedezni a fedezetlent? – Körkép hedge fundokban rejlő lehetőségekről és kockázatokról - Bujtár, Zsolt; Kecskés, András (Debreceni Jogi Műhely, 2015)
The first thing that comes to one’s mind about hedge funds is risk taking and excelled level of profitability. However, the operation of hedge funds is a disputed and sometimes contradicted process and market participants often express their doubt about the effects of the phenomenon. Therfore, the role of legal regulation is crucial at this field. Avoiding the effect of the afore mentioned regulations is however still intended by many funds that operate all over the world. This paper intends to offer a deeper insight in to the world of hedge funds and the regulatory background. In light of the 2007-2009 financial crisis the topic seems to be evergreen and the future of hedge funds largely depends on the application of the regulatory reforms based on the recent experiences.